KAJIAN PENGGUNAAN PERLUASAN MAKNA KETERANGAN SAKSI PADA PERKARA PENGUASAAN NARKOTIKA DENGAN TERSANGKA MRP BIN P - Tri Wahyu Wijanoko; Arsyad Aldyan (Sebelas Maret University, 2021)
This research aims to investigate the use of Constitutional Court Decision Number 65/PUU-VIII/2010 as a legal basis for expanding the meaning of witness testimony in order to convict MRP Bin P, and to understand the reasons why expanding the meaning of witness testimony is necessary in this case. The research method used is doctrinal or normative legal research with a case study approach, and primary and secondary legal sources are collected through literature review techniques. The results of the study show that the lack of evidence in this case makes it difficult for investigators to prove the perpetrator's actions, and expanding the meaning of witness testimony is necessary to overcome this problem. Constitutional Court Decision Number 64/PUU-VIII/2010 provides an opportunity for arresting witnesses to prove the perpetrator's actions of possessing narcotics.Keywords: Narcotics; expansion of meaning; witness statement.